Potential risks of bacterial plant pathogens from thawing permafrost in the Alaskan tundra - Dockyu Kim; Mincheol Kim; Sungho Woo; Sungjin Nam; Nu Ri Myeong; Eungbin Kim; Yung Mi Lee (Ecotoxicology and Environmental Safety)
Global warming-induced permafrost thawing raises concerns about the release of dormant microbes, including potentially harmful plant pathogens. However, the potential pathogenic risks associated with the thawing of permafrost remain poorly understood. Here, we conducted a 90-day soil incubation experiment at 4 °C to mimic extended permafrost thawing in Alaskan tundra soils stratified into active (A), transitional (T), and permanently frozen (P) layers. Following incubation, we examined the changes in bacterial abundance and community composition and tested the reactivation and pathogenicity of dormant plant pathogenic bacteria. Bacterial abundance, measured by colony-forming units and 16S rRNA gene copies, distinctly increased in the T and P layers after thawing. These layers also exhibited substantial shifts in bacterial community structure, with Fe-cycling taxa becoming more abundant and permafrost-dominant taxa decreasing in abundance. Notably, we isolated 52 strains with proteolytic activity, and our pathogenicity tests confirmed that Pseudomonas spp. isolates caused potato soft rot symptoms. Some Pseudomonas pathogens were undetectable in the amplicon sequencing data before thawing and emerged only in the thawed T and P layers. Our findings illustrate that permafrost acts as a reservoir of potential plant pathogens, and their resurgence upon thawing poses a potential risk to Arctic ecosystems.